The paradigm and future value of the metaverse for the intervention of cognitive decline - Zhou, Hao; Gao, Jian-Yi; Chen, Ying (Frontiers in Public Health, 2022)
Cognitive decline is a gradually neurodegenerative process, which is affected by genetic and environmental factors. The doctor-patient relationship in the health-care for cognitive decline is in a "shallow" medical world. With the development of data science, virtual reality, artificial intelligence and digital tweens, the introduction of the concept of the metaverse in medicine brought alternative and complementary strategy in the intervention of cognitive decline. This paper technically analyzes the application scenarios and paradigms of the metaverse in medicine in the field of mental health, including hospital management, diagnosis, prediction, prevention, rehabilitation, progression delay, assisting life, companionship, supervision and so on. The metaverse in medicine made primary progress on education, immersive consultation, dental disease and Parkinson's disease, which brings revolutionary prospects for non-pharmacological complementary treatment of cognitive decline and the other mental problems. In particular, with the demand for non-face-to-face communication generated by the global covid-19 epidemic, the needs for uncontactable health-care service for the elderly are increased. The paradigm of self-monitoring, self-healing and health-care experienced by the elderly through the metaverse in medicine, especially from meta-platform, meta-community, meta-hospital, will be generated, which will reconstruct the service modes for the elderly people. The future map of the metaverse in medicine is huge, which depends on the co-construction of community partners.